2013
DOI: 10.1103/physreve.88.042121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the interplay between initial state and Hamiltonian on the thermalization of isolated quantum many-body systems

Abstract: We explore the role of the initial state on the onset of thermalization in isolated quantum many-body systems after a quench. The initial state is an eigenstate of an initial HamiltonianĤI and it evolves according to a different final HamiltonianĤF . If the initial state has a chaotic structure with respect toĤF , i.e., if it fills the energy shell ergodically, thermalization is certain to occur. This happens whenĤI is a full random matrix, because its states projected ontoĤF are fully delocalized. The results… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 78 publications
3
60
0
Order By: Relevance
“…The results reinforce the equivalence between the two models for the chosen values of d F and λ F . They also corroborate the dependence on temperature in the studies of thermalization [89,90].…”
Section: Thermalizationsupporting
confidence: 83%
See 1 more Smart Citation
“…The results reinforce the equivalence between the two models for the chosen values of d F and λ F . They also corroborate the dependence on temperature in the studies of thermalization [89,90].…”
Section: Thermalizationsupporting
confidence: 83%
“…[90], we studied quenches to the NNN model in the limit of strong perturbation, where the energy distribution of the initial state is Gaussian and therefore already approximately thermal, even before the quench. In such an extreme scenario, it was difficult to clearly discern improvements with T and L. Here, where the initial state is Breit-Wigner, these improvements are more visible.…”
Section: Thermalizationmentioning
confidence: 99%
“…(7.1) is strictly dependent on the following parameters: the width of the strength function in connection with that of the energy shell and the microcanonical energy window. They also make evident that the viability of thermalization depends on the chosen initial state [262,263,264,51] (specifically, close to the edges of the energy band this approach might be not valid). Conventional thermalization is therefore not expected to occur for initial states whose widths of strength functions are smaller than the energy shell.…”
Section: Relaxation Of Few-body Observablesmentioning
confidence: 99%
“…The analysis of how the energy of the initial state affects the viability of conventional thermalization was performed in [262,263,264,51]. In particular, it has been shown that thermalization may happen even in quenches where the final Hamiltonian is integrable provided the initial state spans over chaotic-like states of the total Hamiltonian.…”
Section: Relaxation Of Few-body Observablesmentioning
confidence: 99%
“…The other dimensionality allowing for wellcontrolled studies is ∞D where dynamical mean-field theory becomes exact [19][20][21] and Gutzwiller approaches are well justified [22]. Exact diagonalization is completely flexible concerning dimensionality, but it is restricted to small systems [23,24].…”
Section: Introductionmentioning
confidence: 99%